APPLICATION OF AUGMENTED REALITY BASED ON COGNITIVE CONFLICT AND STEM TO IMPROVE STUDENTS' ATTITUDES IN 21ST CENTURY LEARNING - Agusto, Lukman (Department of Physics Universitas Negeri Padang, 2025)
This research seeks to ascertain the efficacy of incorporating cognitive conflict-based Augmented Reality into STEM curricula on students' views towards the content of Newton's Law of Gravity and Kepler's Law. The method used is pre-experimental with a One-Group Pretest-Posttest design, involving 17 students of phase F of SMA Negeri 1 Candung. The instrument used is an attitude questionnaire adapted from the Colorado Learning Attitudes about Science Survey (CLASS) and has been validated by experts. Data were analyzed using the Shapiro-Wilk normality test and Hypothesis testing using the Paired t-test. The results showed a significant increase in students' attitudes after AR-based learning, with a significance value (p = 0.005) <0.05. These findings indicate that the use of AR integrated with cognitive conflict and the STEM approach shows the potential for a positive impact on students' attitudes in physics learning. With the goals of enhancing students' emotional elements within the framework of 21st century learning, this research adds to the development of technology-based physics learning innovations.